(untitled) (Raparin Journal of Humanities (RJH), 2026)
The aim of this study is to determine the level of teacher self-efficacy and their attitudes about the boycott in general and to determine the relationship between teachers’ self-efficacy and their attitudes about the boycott the research community consisted of 1850 high school teachers in Raperin administration. The sample of the study was 300 male and female teachers randomly selected from the appropriate class. The self-effecacy was consisted of (35) items and (19) items remained after validity and relalibility. The researcher prepared scale for measure (attitudes about bycotte) wgich cosist of (35) items finally after validity and relialibility remained (25) items , The results showed, the level of self-efficacy among high school teachers was generally high. Teachers have positive and high attitudes about boycott and there is no relationship between self-efficacy and attitudes about boycott, finally there is no stastically significance deference about each self-efficacy teachers and attitudes about bycotte according to Gender.